2019
DOI: 10.1002/sdtp.13141
|View full text |Cite
|
Sign up to set email alerts
|

82‐1: Development of Full Roll to Roll Process for Flexible Display Backplane

Abstract: In this article, we described a development of full Roll-to-Roll (R2R) process for flexible display backplane. For many years, we made an effort to convert rigid glass substrates to flexible films for thinness, light weight, flexibility and design freedom. Through Government support program, we have built and stabilized R2R facilities for many years. Amorphous indium-gallium-zinc oxide thin-film transistors (TFTs) with coplanar structure are fabricated using roll type Polyimide film. We have demonstrated the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Recently, demand for higher field-effect mobility (μ FE ) and smaller pixel size has grown as part of efforts to develop next-generation displays with ultrahigh resolution beyond 8 K, a refresh rate greater than 240 Hz, and a pixel density above 1000 pixels per inch. Organic light-emitting diode (OLED) technology, which is dominating the high-end display market, requires a relatively high current density of several microamperes due to the current-driving method of light-emitting devices, unlike that of voltage-driven liquid crystal displays. It is therefore important to precisely understand the self-heating effects in TFTs. Amorphous indium-gallium-zinc oxide ( a -IGZO) is a promising channel material that has been implemented in display backplanes since its invention by Hosono and co-workers in 2004 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, demand for higher field-effect mobility (μ FE ) and smaller pixel size has grown as part of efforts to develop next-generation displays with ultrahigh resolution beyond 8 K, a refresh rate greater than 240 Hz, and a pixel density above 1000 pixels per inch. Organic light-emitting diode (OLED) technology, which is dominating the high-end display market, requires a relatively high current density of several microamperes due to the current-driving method of light-emitting devices, unlike that of voltage-driven liquid crystal displays. It is therefore important to precisely understand the self-heating effects in TFTs. Amorphous indium-gallium-zinc oxide ( a -IGZO) is a promising channel material that has been implemented in display backplanes since its invention by Hosono and co-workers in 2004 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies demonstrate the application of the R2R technique to fabricate various electronic devices, such as thin-film transistors (TFTs) [1][2][3][4], solar cells [5,6], transparent electrode [7][8][9][10], smart sensors [11], printed circuit boards [12], and batteries [13], indicating a high interest in upscaling for mass production. Kook et al [1] demonstrated the world's first 20 inch flexible oxide TFT backplane made with polyimide (PI) film involving deposition, patterning, etch, and inspection processes. Meanwhile, a R2R gravure-printed TFT was shown by Koo et al [2].…”
Section: Introductionmentioning
confidence: 99%